Postnatal care could be the key to improving the continuum of care in maternal and child health in Ratanakiri, Cambodia. - Kimiyo Kikuchi; Junko Yasuoka; Keiko Nanishi; Ashir Ahmed; Yasunobu Nohara; Mariko Nishikitani; Fumihiko Yokota; Tetsuya Mizutani; Naoki Nakashima (PLoS ONE)
In South-East Asia, the maternal and child mortality rate has declined over the past decades; however, it varies among and within the countries in the region, including Cambodia. The continuum of care is an integrated series of care that women and children are required to avail continuously from pregnancy to the child/motherhood period. This study aimed to assess the completion rate of the continuum of care and examine the factors associated with the continuum of care in Ratanakiri, Cambodia. A cross-sectional study was conducted in Ratanakiri. Overall, 377 women were included, and data were collected via face-to-face interviews using a semi-structured questionnaire. Among them, 5.0% completed the continuum of care (antenatal care at least four times, delivery by skilled birth attendant, and postnatal care at least once). Meanwhile, 18.8% did not receive any care during pregnancy, delivery, and after birth. The highest discontinuation rate was at the postnatal care stage (73.6%). Not receiving any perinatal care was associated with neonatal complications at 6 weeks after birth (adjusted odds ratio [AOR]: 3.075; 95% confidence interval [CI]: 1.310-7.215). Furthermore, a long distance to the health center was negatively associated with completion of the continuum of care (AOR: 0.877; 95% CI: 0.791-0.972). This study indicates the need for efforts to reduce the number of women who discontinue from the continuum of care, as well as who do not receive any care to avoid neonatal complications. Since the discontinuation rate was highest at the postnatal care, postnatal care needs to be promoted more through the antenatal care and delivery services. Furthermore, given that long distance to health facilities was a barrier for receiving the care continuously, our findings suggest the need for a village-based health care system that can provide the basic continuum of care in remote areas.